Activation of brain‐derived neurotrophic factor‐tropomyosin receptor kinase B signaling in the pedunculopontine tegmental nucleus: a novel mechanism for the homeostatic regulation of rapid eye movement sleep. Issue 1 (27th January 2017) - Barnes, Abigail K.; Koul‐Tiwari, Richa; Garner, Jennifer M.; Geist, Phillip A.; Datta, Subimal
Abstract: Rapid eye movement (REM) sleep dysregulation is a symptom of many neuropsychiatric disorders, yet the mechanisms of REM sleep homeostatic regulation are not fully understood. We have shown that, after REM sleep deprivation, the pedunculopontine tegmental nucleus (PPT) plays a critical role in the generation of recovery REM sleep. In this study, we used multidisciplinary techniques to show a causal relationship between brain‐derived neurotrophic factor (BDNF)‐tropomyosin receptor kinase B (TrkB) signaling in the PPT and the development of REM sleep homeostatic drive. Rats were randomly assigned to conditions of unrestricted sleep or selective REM sleep deprivation (RSD) with PPT microinjections of vehicle control or a dose of a TrkB receptor inhibitor (2, 3, or 4 nmol K252a or 4 nmol ANA‐12). On experimental days, rats received PPT microinjections and their sleep‐wake physiological signals were recorded for 3 or 6 h, during which selective RSD was performed in the first 3 h. At the end of all 3 h recordings, rats were killed and the PPT was dissected out for BDNF quantification. Our results show that K252a and ANA‐12 dose‐dependently reduced the homeostatic responses to selective RSD. Specifically, TrkB receptor inhibition reduced REM sleep homeostatic drive and limited REM sleep rebound. There was also a dose‐dependent suppression of PPT BDNF up‐regulation, and regression analysis revealed a significant positive relationship between REM sleep homeostatic drive and the level of PPT BDNF expression. These data provide the first direct evidence that activation of BDNF‐TrkB signaling in the PPT is a critical step for the development of REM sleep homeostatic drive. Abstract : REM sleep homeostatic regulation has been associated with emotional regulation and cognitive function, but the mechanism for the generation of REM sleep homeostatic drive is unclear. This study shows that the localized inhibition of TrkB receptors in the pedunculopontine tegmental nucleus (PPT) suppressed the expression of BDNF and blocked REM sleep homeostatic drive. These findings, for the first time, suggest that the activation of BDNF‐TrkB signaling in the PPT is critical for the development of REM sleep homeostatic drive.